Challenges of BIM integration in construction education: The Ghanaian perspective (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Despite the global embrace of BIM as a form of digital transformation in the global construction sector, Ghana remains sluggish in its adoption of this technology, partly due to the scarcity of BIM-trained professionals. This study examines the integration of BIM within construction education curricula in Ghanaian technical universities and identifies the key challenges hindering its integration. A quantitative research methodology was employed, utilizing standardized questionnaires administered to academic staff from five Ghanaian technical universities running construction programs. A total of 59 valid responses were analyzed using SPSS 26 for descriptive statistics to examine the present state of BIM integration in academic curricula. Subsequently, Structural Equation Modeling (SEM) was employed in identifying and validating the critical challenges hindering BIM integration. The findings reveal that BIM integration into construction curricula remains limited, with BIM primarily taught through workshops or partially integrated into existing courses rather than being a standalone course. Key challenges include a lack of faculty expertise and training, limited educational resources, high training costs and inadequate IT infrastructure. SEM results confirmed the significance and interrelated nature of these challenges. Respondents emphasized the need for mandatory inclusion of BIM in curricula to align with global industry standards and to guarantee that graduates are well prepared for the digital challenges present in the construction industry. The study emphasizes importance of aligning educational programs with industry demands to mitigate the skills gap and facilitate the rapid digitalization of Ghana’s construction industry.
Keywords: BIM; Construction education; Technical university; Technology adoption; Technology integration